Pareto efficiency in the model of economy with public goods - Nada Trivić (Anali Ekonomskog fakulteta u Subotici, 2020)
In order to analyze simple and complex models of market, market equilibrium and market efficiency, this article considers a more complex and realistic market model with the existence of public goods. This topic is the subject of attention of many scientists, but only recently has it been possible to apply these models on real life situations and verify their correctness and justifiably. To understand the problems of the existence of public goods on the competitive market better, first one should first understand the nature and characteristics of public goods. Having derived Pareto efficiency criterion with the presence of public goods, the article attempts to answer the question whether there is an economy where competitive behavior may result in an efficient solution.